Upaya Keharmonisan Keluarga Pasangan Suami Istri Tanpa Keturunan di Kelurahan Tonatan Ponorogo Perspektif Keluarga Sakinah - Azzuhri, Muhammad Ridwan; Aini, Shofwatul (Jurnal Antologi Hukum, 2025)
Every married couple desires family harmony and offspring, as offspring are the bond between husband and wife and the foundation for the family. However, not all couples achieve childbearing easily. Some couples struggle, or even fail to conceive, even after a long marriage. This can disrupt family harmony, as childless couples often experience social pressure. In this situation, childless couples are highly susceptible to infidelity, polygamy, and arguments that ultimately lead to divorce. However, not all childless couples end in divorce, as is the case with childless couples in Tonatan, Ponorogo. This study aims to explore the meaning of a harmonious family among childless couples and the efforts of childless couples to maintain or realize family harmony. The method used in this study is a qualitative field study. This study resulted in the understanding of the concept of a harmonious family among childless couples in Tonatan, Ponorogo District, which has developed significantly beyond existing theories. They define a harmonious family as a happy, comfortable, peaceful, and serene family. This couple also strives to make their family a harmonious one, including accepting and complementing each other's shortcomings, communicating and deliberating, having a strong religious belief, implementing marital advice, harmonizing views, and caring for adopted children as if they were their own.